AEROENGINE - TAYLOR MARK DAVID; HOWARTH NICHOLAS; PARRY ANTHONY BRIAN (2013)
PROBLEM TO BE SOLVED: To provide a method of operating a counter-rotating propeller engine having front and rear propellers to decrease the whole noise generated by the propeller.SOLUTION: The engine 10 is operated during at least a take-off phase, a climb phase, a cruise phase and an approach phase; and during the cruise phase, the engine operates with a generally constant propeller tip speed. The method comprises the step of operating the engine such that the tip speed of at least one of the propellers 23 and 24, during at least one of the take-off phase, the climb phase or the approach phase, may greater the tip speed greater than the cruise phase tip speed to reduce the overall noise generated by the propellers.